The First Commanderies of the Templars on Polish Lands: Reasons and Time of Appearance - Саєнко, Анастасія (Київський національний університет імені Тараса Шевченка, 2023)
Introduction. Throughout the 13th century, the Order of the Templars actively strengthened their positions in Europe, particularly in its Central-Eastern part. The relevance of the study lies in understanding the reasons and context for the expansion of the Templar Order's influence on this region, considering the geopolitical, economic, and socio-cultural environment of the time. The aim is to analyze the causes of the Templars' emergence and the initial phase of their activity in Polish territories based on sources and specialized historical literature. Methods. The scientific research is based on the principles of historicism and scientific approach, and it includes general scientific methods of analysis, synthesis, generalization, and comparison, as well as specialized historical (typological and systematic historic) methods. Research Results. Key factors for the appearance of the Templar Order in Poland were identified: the interest of the Polish aristocracy in the Crusades, colonization, and economic initiatives aimed at strengthening the Order's positions on the global stage. The Order developed an infrastructural network by establishing commanderies for optimizing management and economic activity, which facilitated the growth of the Order's network in both military and economic contexts. Conclusions. In the 13th century, the Templar Order expanded its influence onto Polish territory, which was of strategic importance due to its proximity to key Central European states (Holy Roman Empire, Bohemia, Slovakia, and the Galicia-Volhynia Principality). The Polish leadership supported the Templars, granting them land privileges, which helped establish their presence through a network of commanderies. Moreover, the Templars intensified their economic and trade operations, becoming a key element in the medieval economy of the region. The combination of strategic, economic, and political factors contributed to the Templar Order's establishment in Poland. DOI: https://doi.org/10.17721/1728-2640.2023.156.5

Вступ. Протягом ХІІІ ст. орден тамплієрів активно зміцнював свої позиції в Європі, зокрема в центрально-східній її частині. Актуальність дослідження полягає у розумінні причин та контексту розширення впливу Ордену храмовників на цей регіон, враховуючи геополітичне, економічне і соціокультурне середовище того часу. Мета – на основі джерел та спеціальної історичної літератури проаналізувати причини появи та початковий етап діяльності ордену тамплієрів на польських землях. Методи. Наукове дослідження ґрунтується на принципах історизму та науковості, а також включає загальнонаукові методи аналізу, синтезу, узагальнення та порівняння та спеціально-історичні методи, такі як історико-типологічний та історико-системний. Результати дослідження. Виявлено ключові чинники появи Ордену тамплієрів у Польщі: зацікавленість польської аристократії у хрестових походах, колонізаційні та економічні ініціативи, орієнтовані на зміцнення позицій ордену на світовій арені. Орден розвивав інфраструктурну мережу, створюючи командорства для оптимізації управління та економічної активності, що сприяло розвитку мережі Ордену як у військовому, так і в економічному контексті. Висновки. У ХІІІ ст. Орден тамплієрів розширив свій влив на територію Польщі, як стратегічно важливої зони через її сусідство з ключовими державами Центральної Європи (Священною Римською імперією, Чехією, Словаччиною та Галицько-Волинським князівством.). Польське керівництво підтримувало тамплієрів, надаючи їм земельні привілеї, що сприяло встановленню їхньої присутності через створення мережі командорств. Водночас тамплієри активізували економічні та торговельні операції, стаючи ключовим елементом середньовічної економіки регіону. Поєднання стратегічних, економічних та політичних факторів сприяло утвердженню ордену у Польщі. DOI: https://doi.org/10.17721/1728-2640.2023.156.5
Перші командорства тамплієрів на польських землях: причини та час появи
Keywords: Middle Ages; Order of the Templars; military monastic orders; Poland; crusaders; Templars; Middle Ages; Order of the Templars; military monastic orders; Poland; crusaders; Templars; Середньовіччя; орден тамплієрів; військово-чернечі ордени; Польща; хрестоносці; тамплієри; орден тамлієрів; середньовіччя; військово-чернечі ордени; хрестоносці